Investigating the hydro-mechanical behaviour of unsaturated sand-bentonite mixtures using suction-controlled triaxial test - Wael M. Albadri; Israa J. Alhani; Hussein A. Shaia; Mohanad Muayad Sabri Sabri; Sin Mei LIM; Mohanad Sameer Jabbar; Murtadha Saeed Mohammed (Case Studies in Construction Materials, 2023)
Soil improvement is often done through mixing the granular soils with fine-grained materials to obtain densified soil matrix and eventually increase the bearing capacity of the soil. In this paper, sand was mixed with three different quantities of bentonite. Then, the hydromechanical behaviour of sand-bentonite mixtures was evaluated at different matric suctions. Suction-controlled triaxial test and the pressure plate extractor were used to obtain the experimental data needed to derive the stress-strain curves and the Soil Water Characteristics Curve (SWCC), respectively. The results showed that the apparent cohesion that developed due to the existence of matric suction was increasing with the bentonite content increase. Residual suction value was increasing as the bentonite content increasing. It was concluded that the increase of water retention capacity has made the sand-bentonite samples responds very significantly with changing of matric suction. Therefore, addition of fine materials to granular soils would make the soil prone to wetting collapse upon reaching the saturation condition during the rainy seasons.